2005
DOI: 10.1051/0004-6361:20041715
|View full text |Cite
|
Sign up to set email alerts
|

Extra-planar H I in the starburst galaxy NGC 253

Abstract: Abstract.Observations of the nearby starburst galaxy NGC 253 in the 21-cm line reveal the presence of neutral hydrogen in the halo, up to 12 kpc from the galactic plane. This extra-planar H  is found in only one half of the galaxy and is concentrated in a half-ring structure and plumes which are lagging in rotation with respect to the disk. The H  plumes are seen bordering the bright Hα and X-ray halo emission. It is likely that, as proposed earlier for the Hα and the X-rays, the origin of the extra-planar H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 24 publications
10
85
0
Order By: Relevance
“…The shape of the radio halo in our MWA radio images (Figure 2) resembles the "horn-like" or "X-shaped" structure seen at gigahertz radio frequencies , in H I (Boomsma et al 2005;Lucero et al 2015), X-rays (Fabbiano 1988;Pietsch et al 2000;Bauer et al 2008), Hα (G. Meurer, private communication; Figure 2), UV (Hoopes et al 2005), and far-IR (Kaneda et al 2009). …”
Section: Halo Morphologysupporting
confidence: 59%
“…The shape of the radio halo in our MWA radio images (Figure 2) resembles the "horn-like" or "X-shaped" structure seen at gigahertz radio frequencies , in H I (Boomsma et al 2005;Lucero et al 2015), X-rays (Fabbiano 1988;Pietsch et al 2000;Bauer et al 2008), Hα (G. Meurer, private communication; Figure 2), UV (Hoopes et al 2005), and far-IR (Kaneda et al 2009). …”
Section: Halo Morphologysupporting
confidence: 59%
“…This cycle (i.e., the expulsion and the rain-back of gas) could be responsible for the assembly of an extra-planar gas reservoir. This process could be somewhat analogous to that observed with deep observations of HI 21 cm line emission in several nearby disk galaxies, where neutral hydrogen gas is deposited into the galaxy's halo environment mainly by stellar feedback (in the most extreme cases out to a few tens of kpc above the main galaxy disk; e.g., Fraternali et al 2002Fraternali et al , 2005Boomsma et al 2005;Oosterloo et al 2007;Fraternali & Binney 2008). This extra-planar neutral gas is characterized by slower rotation compared to the galaxy disk (most pronounced at small galactic radii), it can have an asymmetric distribution, and it may contain up to ∼10 9 M of neutral gas (in some cases up to ∼30% of the galaxy's total HI content; see Oosterloo et al 2007;Boomsma et al 2008 for examples).…”
Section: Outflow Mass Rate and The Ism/igm Metal Enrichmentsupporting
confidence: 59%
“…Superwind cones are commonly observed in X-rays, radio continuum and Hα but infrequently in HI. In the case of NGC 253, HI has been observed to be confined within the optical disk and to outline the superwind cone of ionized gas in one half of the galaxy (Boomsma et al 2004). Another study has shown that significant amounts of HI is observed to be in the halos of spiral galaxies with active star formation (Fraternali et al 2001).…”
Section: Starburst Driven Superwindmentioning
confidence: 99%